CHINA AND THE REFORM OF THE INTERNATIONAL ECONOMIC SYSTEM - Yana Leksyutina (Сравнительная политика, 2018)
The 2008 global financial crisis has become a turning point for the world community to realize the necessity to reform international economic system and to allow greater participation of leading emerging economies in the global economic governance. Given the huge economic might that China has accumulated and its willingness to assume greater international responsibilities and leadership functions, China can be regarded as one of the countries that play a key role in the processes of reforming the international economic system and global economic governance. Contributing to the improvement of the existing rules, norms and institutions, Beijing at the same time offers to the world its new, China-centered initiatives, to name a few, the Asian Infrastructure Investment Bank and “Belt and Road” Initiative. This article characterizes China’s participation in the reforming of the international economic system after the 1997 Asian financial crisis till the present time with the focus on identifying major forms of China’s participation, its motivations and efforts’ emphasis. By reviewing initiatives and measures that China offers, backs and conducts in order to bring changes into the international economic system and by analyzing Chinese leadership’s official rhetoric and foreign policy activities, the article concludes that Beijing has set a course to assume one of the key roles in the global economic governance and to create China-dominated system of international rules, norms and institutions.